2014
DOI: 10.7860/jcdr/2014/6599.4205
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Asymptomatic Bacteriuria and its Antibacterial Susceptibility Pattern Among Pregnant Women Attending the Antenatal Clinic at Kanpur, India

Abstract: IntrOductIOnUrinary Tract Infections (UTIs) commonly occur pregnancy, due to the morphological and physiological changes that take place in the genitourinary tract. UTIs are of two types, symptomatic and asymptomatic. Asymptomatic Bacteriuria (ASB) is defined as the presence of actively multiplying bacteria, which is greater than 105/ ml of urine within the urinary tract, excluding the distal urethra, at a time when the patient has no symptoms of a UTI [1]. ASB can be found in both pregnant and non-pregnant wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

40
77
4
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(127 citation statements)
references
References 12 publications
40
77
4
6
Order By: Relevance
“…These finding is similar to other reports which suggest that Gram-negative bacteria, particularly E. coli is the most common pathogen isolated in patients with UTI [2,5,[44][45][46][47]. The pattern of infection by E. coli, S. aureus and K. pneumoniae obtained in this study is in agreement with other study reported by [17], showing similar infection rate and pattern where E. coli (51.2%), S. aureus (27.3%), and K. pneumoniae (12.8%) respectively.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…These finding is similar to other reports which suggest that Gram-negative bacteria, particularly E. coli is the most common pathogen isolated in patients with UTI [2,5,[44][45][46][47]. The pattern of infection by E. coli, S. aureus and K. pneumoniae obtained in this study is in agreement with other study reported by [17], showing similar infection rate and pattern where E. coli (51.2%), S. aureus (27.3%), and K. pneumoniae (12.8%) respectively.…”
Section: Discussionsupporting
confidence: 82%
“…The pattern of infection by E. coli, S. aureus and K. pneumoniae obtained in this study is in agreement with other study reported by [17], showing similar infection rate and pattern where E. coli (51.2%), S. aureus (27.3%), and K. pneumoniae (12.8%) respectively. However, the 13.2% incidence rate of K. pneumoniae reported in this study is consistent with previous study [7], also this bring K. pneumoniae as predominant organism in UTI which lay out different status for this organism which disagree with other studies reported by [5,[48][49][50]. Adding to that prevalence of S. aureus in UTI in this study is in agreement with other reports [8], but disagrees with earlier study by [51].…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations